Analisis Perbandingan Kinerja Routing Ospf Multi Area IP Versi 4 dan Routing OSPF V3 IP Versi 6 Pada Mikrotik OS Simulasi GNS3 - Almayadi Pratama; Ilham Faisal; Divi Handoko (LKP Unity Academy, 2024)
Large-scale and multi-area networks with quite a lot of routers are certainly very inconvenient if there is no appropriate routing protocol management. One of the reliable routing protocols for distributing routing with quite a lot of routers is the Open Shortest Path First (OSPF) protocol. However, there are 2 types of OSPF on IP version 4 and IP version 6, where on IP version 6 OSPF was developed into OSPF V3, making it difficult for network admins to determine which OSPF quality is better in routing protocols. Therefore, in this study, a comparison was made with the GNS3 simulation to determine the best routing protocol between OSPF IP version 4 and OSPF V3 IP version 6. especially the delay time for IPv4 496ms, IPv6 438ms and packet loss for IPv4 19.74% while IPv6 is 11.97%. Keywords: Routing, OSPF, OSPF V3, IPv4, IPv6